2020
DOI: 10.1002/adem.201901217
|View full text |Cite
|
Sign up to set email alerts
|

Toward High‐Throughput Texturing of Polymer Foils for Enhanced Light Trapping in Flexible Perovskite Solar Cells Using Roll‐to‐Roll Hot Embossing

Abstract: A path to further increase the power conversion efficiency of perovskite solar cells is maximizing sunlight absorption using patterned substrates with enhanced light-trapping capabilities. However, to be competitive with traditional solar cells, especially in niche markets, low-cost texturing methods have to be developed. Herein, a roll-to-roll hot embossing method to pattern flexible polyethylene terephthalate (PET) foils is presented as a proof of concept. The cylindrical mold for the embossing process is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 65 publications
(104 reference statements)
0
27
0
Order By: Relevance
“…surface topography of the metallic tools to polymer foils at processing speeds of several square meters per minute (Soldera et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…surface topography of the metallic tools to polymer foils at processing speeds of several square meters per minute (Soldera et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…In addition, the scale‐up of such technologies for industrial applications has been already demonstrated in several cases. [ 31–34 ]…”
Section: Introductionmentioning
confidence: 99%
“…This shift could be a result of the reduced trap density due to the passivation effect of the triethylene glycol side chains attached to the polymers. [50][51][52][53] 3 | CONCLUSION In summary, we synthesized polythiophene SCPs by the random copolymerization of two units, namely 2R-BT and TEG-T, in different ratios. In comparison with the homopolymer synthesized 2R-BT (P0), the optimized random polymer P20 was observed to exhibit increased crystal orientation randomness, denser packing, and more homogeneous surface morphology.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the perovskite films with P10, P20, and P30 random copolymers exhibited more blue‐shifted PL emission peaks at 801 nm in comparison with the homopolymer P0 (803 nm). This shift could be a result of the reduced trap density due to the passivation effect of the triethylene glycol side chains attached to the polymers 50‐53 …”
Section: Resultsmentioning
confidence: 99%